Evaluation of oil palm frond for biobutanol production by different Clostridia species - Abubakar, Abdurrahman; Md Salleh, Madihah; Yahya, Adibah; Hussin, Huszalina; Shiong, Chong Chun; Mohamad, Shaza Eva; Abd Aziz, Suraini (Lembaga Minyak Sawit Malaysia, 2024)
Ideal substrates and biobutanol producers are the key and most important ingredients for efficient biobutanol production. In this research, we evaluated the composition of oil palm fronds based on the different ages of the plant. Fresh oil palm frond (OPF) juice was found to be the most potent OPF component for biobutanol production and was pressed from 5, 10, 15 and 20 years old trees using a sugarcane pressing machine. The total sugar concentrations were estimated by the use of a DNS and spectrophotometer and were found to be decreasing with the increasing age of the palm oil tree, with the highest sugar obtained at OPF ages 5 and 10. HPLC analysis revealed that glucose was the highest fraction in the juice, accounting for 57% to 66%, while fructose (12%-17%) and sucrose (19%-25%) made up the remaining percentage. Fermentation inhibitors like gallic and ferulic acids were also detected in the juice using the HPLC technique, and their concentrations also increased with age. Therefore, the research screened for a robust bacterial strain that can tolerate these phenolics in the hydrolysate for biobutanol production. Out of the 11 strains of Clostridium screened, strain A1 was found to successfully utilise the hydrolysate and yield the highest concentration of biobutanol at 2.32 g/L with the productivity of 0.064 g/L/hr. The strain was identified as Clostridium strain A1 based on 16S rRNA gene sequencing techniques.